Faktor-faktor yang Mempengaruhi Minat Penggunaan Ulang Maxim - Desy Amalia Candrakusuma; Mutty Claudia Dewinda (Jurnal Akuntansi dan Pajak, 2024)
The use of transportation services in leading urban areas, such as Surakarta, which excel in tourism, education, economy, and trade, is increasing rapidly. Transportation service companies are taking the opportunity to improve technology by creating online transportation. Cities that have a high need for online transportation services mean that every company must increase interest in reusing online transportation so that the online transportation service company can compete with its competitors, including the online transportation service company Maxim. This study aims to determine the factors that influence interest in reusing Maxim transportation. The sample for this research was 105 students at the University of Surakarta. This study used multiple linear regression analysis. The data collection method was done through a questionnaire with purposive sampling technique. The research findings show that price and service quality have a positively and significantly on the interest in reusing Maxime transportation. Discount have a negative and significant effect on interest in reusing Maxime transportation. Meanwhile, promotion have no effect on interest in reusing Maxime transportation. Keywords: Perceptions of Price, Discounts, Promotions, Service Quality, and Intention to Reuse